Work Family Conflict In Honorary Teachers: A Study Of Causes, Impacts And Coping Strategies - Alfiyanah; Rahmawati Prihastuty (Journal of Social and Industrial Psychology, 2024)
This research aims to identify the causes of work-family conflict experienced by working women. Additionally, it aims to identify the impacts experienced by the working women themselves, their families, and their institutions. Furthermore, the research aims to identify coping strategies used by honorary teachers to deal with work-family conflict. The research utilizes a qualitative descriptive approach with a phenomenological study approach. The results of the research indicate that sources of work-related issues include long working hours, time constraints, internal office conflicts, and demanding workloads. On the other hand, family-related conflicts stem from household situation characteristics such as heavy household chores, absence of domestic help, and the husband's irregular job or income. The impacts experienced by honorary teachers include psychological pressure and health issues. The impact on the family includes feelings of neglect. There are several coping strategies used by honorary teachers to overcome work-family conflict, which are a combination of emotion-focused coping and problem-focused coping strategies